Program design based on a mathematical model using Rating of Perceived Exertion for an elite Japanese sprinter: A case study - Suzuki, S.; Sato, T.; Maeda, A.; Takahashi, Y. (The Journal of Strength and Conditioning Research, 2006)
The study investigated the effects of program design on 400-m sprint time by applying a Rating of Perceived Exertion (RPE) mathematical model to training performance. The subject was 24 years old and had been training for 9 years. His best performance in 400-m sprint competitions was 45.50 seconds. Body weight, resting heart rate, training time and RPE were monitored daily after training sessions. Similarly, performance in 400-m races was recorded 9 times during 2003. At the World Championships in Athletics in France, the subject's team placed eighth in the 1,600-m relay. The RPE mathematical model was able to predict changes in performance. Rate of matching was statistically significant (r2 = 0.83, F ratio = 34.27, p < 0.001). Application of the RPE mathematical model to the design of a training program specific to the needs of a 400-m sprinter indicates a potentially powerful tool that can be applied to accurately assess the effects of training on athletic performance.